Updates in Volcanology New Advances in Understanding Volcanic Systems - Nemeth, Karoly (IntechOpen, 2012)
This book is the second volume of the Updates in Volcanology and presents review style chapters as well as stand alone research works on volcanological problems that could be used as valuable resource for both researchers and graduate research students. The book presents chapters arching over a broad field of volcanology among many are considered to be dynamically developing subject areas such as volcano morphology, volcanic terrain evolution or volcaniclastic-hosted mineral resource analysis. The book also takes the reader to areas such as the Russian Far East or sedimentary basins in China which are very remote and generally less known for the global community. This book demonstrates the dynamic evolution of volcanology in the past decades.